Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 28811 by abdo imad last updated on 30/Jan/18

find ∫_0 ^∞ ln(1+e^(−xt) )dx with t>0 then give the value of  ∫_0 ^∞ ln(1+e^(−x) )dx.

find0ln(1+ext)dxwitht>0thengivethevalueof 0ln(1+ex)dx.

Commented byabdo imad last updated on 01/Feb/18

we havefor ∣u∣<1  (d/du)(ln(1+u))= (1/(1+u))= Σ_(n=0) ^∞ (−1)^n u^n  ⇒  ln(1+u)= Σ_(n=0) ^∞  (((−1)^n )/(n+1))u^(n+1 )   +k       (k=ln(1)=0) so  ln(1+u)= Σ_(n=1) ^∞   (((−1)^(n−1) )/n) u^n    and  ∫_0 ^∞ ln(1+ e^(−xt) )dx =∫_0 ^∞ (Σ_(n=1) ^∞  (((−1)^(n−1) )/n) e^(−nxt) )dx  = Σ_(n=1) ^∞   (((−1)^(n−1) )/n) ∫_0 ^∞  e^(−ntx) dx= Σ_(n=1) ^∞   (((−1)^(n−1) )/n)  A_n   A_n = ∫_0 ^∞   e^(−ntx) dx = ((−1)/(nt)) [  e^(−ntx) ]_(x=0) ^∞ = (1/(nt)) so  ∫_0 ^∞ ln(1+ e^(−xt) )dx=  (1/t) Σ_(n=1) ^∞    (((−1)^(n−1) )/n^2 )=−(1/t)δ(2)  δ(x)= Σ_(n=1) ^∞  (((−1)^n )/n^x ) we have proved that  δ(x)=( 2^(1−x)  −1)ξ(x) ⇒δ(2)= ((1/2) −1)ξ(2)=−(1/2) (π^2 /6)  =−(π^2 /(12))  and ∫_0 ^∞ ln(1+ e^(−xt) )dx= (π^2 /(12t))   let take t=1  ∫_0 ^∞  ln(1+ e^(−x) )dx =(π^2 /(12)) .

wehaveforu∣<1ddu(ln(1+u))=11+u=n=0(1)nun ln(1+u)=n=0(1)nn+1un+1+k(k=ln(1)=0)so ln(1+u)=n=1(1)n1nunand 0ln(1+ext)dx=0(n=1(1)n1nenxt)dx =n=1(1)n1n0entxdx=n=1(1)n1nAn An=0entxdx=1nt[entx]x=0=1ntso 0ln(1+ext)dx=1tn=1(1)n1n2=1tδ(2) δ(x)=n=1(1)nnxwehaveprovedthat δ(x)=(21x1)ξ(x)δ(2)=(121)ξ(2)=12π26 =π212and0ln(1+ext)dx=π212tlettaket=1 0ln(1+ex)dx=π212.

Terms of Service

Privacy Policy

Contact: info@tinkutara.com